Transient Corneal Edema is a Predictive Factor for Pseudophakic Cystoid Macular Edema after Uncomplicated Cataract Surgery - Do, Jae Rock; Oh, Jong-Hyun; Chuck, Roy S.; Park, Choul Yong (Korean journal of ophthalmology, 2015)
To report transient corneal edema after phacoemulsification as a predictive factor for the development of pseudophakic cystoid macular edema (PCME). A total of 150 eyes from 150 patients (59 men and 91 women; mean age, 68.0 ± 10.15 years) were analyzed using spectral domain optical coherence tomography 1 week and 5 weeks after routine phacoemulsification cataract surgery. Transient corneal edema detected 1 week after surgery was analyzed to reveal any significant relationship with the development of PCME 5 weeks after surgery. Transient corneal edema developed in 17 (11.3%) of 150 eyes 1 week after surgery. A history of diabetes mellitus was significantly associated with development of transient corneal edema (odds ratio [OR], 4.04; 95% confidence interval [CI], 1.41 to 11.54; p = 0.011). Both diabetes mellitus and transient corneal edema were significantly associated with PCME development 5 weeks after surgery (OR, 4.58; 95% CI, 1.56 to 13.43; p = 0.007; and OR, 6.71; CI, 2.05 to 21.95; p = 0.003, respectively). In the 8 eyes with both diabetes mellitus and transient corneal edema, 4 (50%) developed PCME 5 weeks after surgery. Transient corneal edema detected 1 week after routine cataract surgery is a predictive factor for development of PCME. Close postoperative observation and intervention is recommended in patients with transient corneal edema.